Adult phenotype in Koolen-de Vries/KANSL1 haploinsufficiency syndrome. Issue 2 (24th December 2020) - Amenta, Simona; Frangella, Silvia; Marangi, Giuseppe; Lattante, Serena; Ricciardi, Stefania; Doronzio, Paolo Niccolò; Orteschi, Daniela; Veredice, Chiara; Contaldo, Ilaria; Zampino, Giuseppe; Gentile, Mattia; Scarano, Emanuela; et al.
Abstract : Background: Koolen-de Vries syndrome (KdVS) is a multisystem neurodevelopmental disorder caused by 17q21.31 deletions or mutations in KANSL1 . It was mainly described in children. Methods: A retrospective study on 9 subjects aged 19–45 years and revision of 18 literature patients, with the purpose to get insights into the phenotypic evolution with time, and into the clinical manifestations in adulthood. Results: Seven patients had a 17q21.31 deletion and two a point mutation in KANSL1 . All had intellectual disability, which was mild in five (56%) and moderate in four (44%). Epilepsy was diagnosed in four subjects (44%), with onset from 1 to 7 years and full remission before 9 years in 3/4 patients. Scoliosis affected seven individuals (77.7%) and it was substantially stable with age in 5/7 patients, allowing for simple daily activities. Two subjects had severely progressive scoliosis, which was surgically corrected. Overweight or true obesity did occur after puberty in six patients (67%). Behaviour abnormalities were recorded in six patients (67%). The facial phenotype slightly evolved with time to include thick eyebrows, elongated nose and pronounced pointed chin. Despite behaviour abnormalities, happy disposition and sociable attitudes were common. Half of patients had fluent language and were good at writing and reading. Rich language, although limited to single words or short sentences, and very limited or absent skills in writing and reading were observed in the remaining patients. Autonomy in daily activities and personal care was usually limited. Conclusions: Distinctive features in adult KdVS subjects include intellectual disability, overweight/obesity, behaviour abnormalities with preserved social interest, ability in language, slight worsening of the facial phenotype and no seizures.